Seigneurial Worries of the “principal senhor destes reynos”. The Legacy of Teodósio I, 5th Duke of Braganza - Soares da Cunha, Mafalda (Cuadernos de Historia Moderna, 2017)
This text focuses on the managerial legacy of Teodósio), 5th Duke of Braganza (1532-1563), with regard to his Duchy. It brings to the fore how much his governance regarding family, house and estate impacted on the future of the duchy; how, despite having strengthened the position of the Braganza Dukedom as the most important seigneurial House of Portugal which boasted its own court system in Vila Viçosa (Alentejo) and its own network of dependent noble houses, thus mirroring the style of the Portuguese Royal Household, D. Teodósio’s choices also contributed a great deal to the indebtedness of the House of Braganza; and lastly, how these decisions contributed to the political developments in the Portuguese Kingdom, namely in the events pertaining to the 1580 and 1640.
Keywords: Portuguese Nobility; Seigneurial Courts; House of Bragança; Teodósio I; 5th duke of Braganza